Altered Differential Control of Sympathetic Outflow Following Sedentary Conditions: Role of Subregional Neuroplasticity in the RVLM - Subramanian, Madhan; Mueller, Patrick J. (Frontiers in Physiology, 2016)
Despite the classically held belief of an “all-or-none” activation of the sympathetic nervous system, differential responses in sympathetic nerve activity (SNA) can occur acutely at varying magnitudes and in opposing directions. Sympathetic nerves also appear to contribute differentially to various disease states including hypertension and heart failure. Previously we have reported that sedentary conditions enhanced responses of splanchnic SNA (SSNA) but not lumbar SNA (LSNA) to activation of the rostral ventrolateral medulla (RVLM) in rats. Bulbospinal RVLM neurons from sedentary rats also exhibit increased dendritic branching in rostral regions of the RVLM. We hypothesized that regionally specific structural neuroplasticity would manifest as enhanced SSNA but not LSNA following activation of the rostral RVLM. To test this hypothesis, groups of physically active (10-12 weeks on running wheels) or sedentary, male Sprague-Dawley rats were instrumented to record mean arterial pressure, LSNA and SSNA under Inactin anesthesia and during microinjections of glutamate (30 nl, 10 mM) into multiple sites within the RVLM. Sedentary conditions enhanced SSNA but not LSNA responses and SSNA responses were enhanced at more central and rostral sites. Results suggest that enhanced SSNA responses in rostral RVLM coincide with enhanced dendritic branching in rostral RVLM observed previously. Identifying structural and functional neuroplasticity in specific populations of RVLM neurons may help identify new treatments for cardiovascular diseases, known to be more prevalent in sedentary individuals.